The Role of The Tourism Sector in Post Pandemi Covid-19 Economic Growth - Heru Widodo; Machin Machin; Ahmad Sukendi; Hevy Susanti (JOURNAL OF SHARIA ECONOMICS, 2022)
The purposes of this study are 1. To find out the Condition of the Tourism Sector in Lamongan Regency After the Covid-19 Pandemic, 2. To find out the Role of the Tourism Sector in Lamongan Regency's Economic Growth After the Covid-19 Pandemic. the research that will be used is analytical research with a qualitative approach. This research was conducted in Lamongan Regency. With an allocation of 3 months starting in mid-March, April, May 2022. Data collection techniques are through observation, documentation and interviews (Interview). In this study, the analytical method used is descriptive method with a qualitative approach. The results of the study are as follows: 1. The condition of the Tourism Sector in Lamongan Regency After the Covid-19 Pandemic has experienced an increase in the number of visitors and financial income from entrance tickets, parking and hotels/inns, restaurants/eateries and shopping for souvenirs typical of Lamongan. The Role of the Tourism Sector in the Economic Growth of Lamongan Regency After the Covid-19 Pandemic is by providing contributions to PAD